Фотоперестроювання частоти ХРК-лазера i шляхи його оптимiзацiї - Ilchishin, I. P.; Mykytiuk, T. V. (Publishing house "Academperiodika", 2019)
The results of our research of the phototuning of a lasing frequency in induced cholesteric liquid crystals (CLC) by changing the concentration of photoisomer molecules of the CLC with azo- and azoxy-groups in impurities twisting the nematic and in the nematic itself at a selective irradiation are presented. When using nematics with azoxy-groups of the ZhK-654 type, in which the twisting impurities were cholesterol esters (without photoisomers), the conditions to minimize the lasing threshold and to expand the phototuning frequency range are investigated. The influence of the quality of a liquid crystal orientation on the lasing threshold and the phototuning frequency range is studied. The obtained time of the phototuning of a lasing frequency was tens of minutes due to the proximity of the absorption bands of both stereoisomers and their small size. We have decreased the phototuning time, by using a highly sensitive twisting impurity, which absorbs light at the frequency of the exciting laser. The lasing in such induced CLC is got for the first time. The record time of the tuning of the lasing wavelength (21 nm for 148 ms) is obtained under the irradiation of a laser diode with a wavelength of 532 nm. Thus, we have reduced the phototuning time by almost 3 orders in comparison with the known CLC-materials.